Depression Among Medical Students at Derna University Following Hurricane Daniel - Arej Salem,; Amenh Yousif,; Nada Sadaqah,; Abdelsalam Abuzreda,; Hadeel Elhamss,; Hudi Aboukhsheem, (AlQalam Journal of Medical and Applied Sciences, 2025)
Medical students are a vulnerable population for mental health disorders. This vulnerability can be severely worsened by large-scale traumatic events. Hurricane Daniel devastated the city of Derna, Libya, in September 2023, causing massive loss of life and destruction. This study aimed to assess the prevalence of depression and self-esteem and identify associated factors among medical students at the University of Derna following this catastrophe. A cross-sectional study was conducted from August to December 2024 among 266 medical students selected via a purposive sampling technique. Data were collected using an online-administered questionnaire that included a socio-demographic section, details about hurricane exposure, the Beck Depression Inventory (BDI), and the Coopersmith Self-Esteem Inventory (SEI). Non-parametric tests (Mann-Whitney U, Kruskal-Wallis) were used for data analysis, with statistical significance set at p < 0.05. The study revealed an alarming prevalence of depression, with 79.3% of students exhibiting clinically significant symptoms. Nearly two-thirds (63.9%) experienced moderate-to-severe depression. Low self-esteem was found in 42.1% of participants. The hurricane exposure was extensive: 83.5% of students lost a close friend, 30.5% lost a family member, 38.4% were present in the affected area during the hurricane, and 36.1% were displaced. Academically, 89.9% reported that their studies were negatively impacted. Male students had significantly higher depression scores than females (p=0.033). Significant differences were also found across academic years, with third-year students being the most vulnerable (highest depression, lowest self-esteem) and fourth-year students the most resilient (lowest depression, highest self-esteem). The data indicate that in the aftermath of Hurricane Daniel, medical students at the University of Derna faced a severe mental health crisis characterized by extremely high rates of depression and widespread academic disruption. The findings highlighted male students and those in their third academic year as particularly vulnerable groups. These results underscore the urgent need for targeted mental health interventions, trauma-informed counseling, and robust support systems to aid the recovery of these future physicians.